2021
DOI: 10.1111/ijcs.12645
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review on the supply chain agility for manufacturer and consumer

Abstract: For a company to survive in the long run, it is necessary to attract enough customers to generate profitability. Since the high uncertainty in organizations requires a more rapid response to customers’ needs, agility is a critical success factor for today’s manufacturing enterprise. To be competitive, enterprises must integrate their supply chains more effectively and forge close memberships with customers and suppliers more quickly. Therefore, the current study attempts to understand how supply chain agility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 89 publications
3
16
0
Order By: Relevance
“…Du et al. 's (2021) review on supply chain agility using the PRISMA protocol and 35 articles from 21 CABS AJG‐ranked journals highlights the changes in consumer requirements, competition, marketplace, society, and technology, and how companies can respond to these changes to develop supply chain agility, which can create or preserve competitive advantages and produce positive impacts on consumer satisfaction, market share, profitability, sales, and velocity to market.…”
Section: Exemplars Of Systematic Literature Reviewsmentioning
confidence: 99%
“…Du et al. 's (2021) review on supply chain agility using the PRISMA protocol and 35 articles from 21 CABS AJG‐ranked journals highlights the changes in consumer requirements, competition, marketplace, society, and technology, and how companies can respond to these changes to develop supply chain agility, which can create or preserve competitive advantages and produce positive impacts on consumer satisfaction, market share, profitability, sales, and velocity to market.…”
Section: Exemplars Of Systematic Literature Reviewsmentioning
confidence: 99%
“…ey used Red Deer Algorithm (RDA) to optimize this model. Du et al [17] presented a systematic literature review on supply chain agility. In this study, the evolution of the concept of the agile supply chain has been investigated, and a systematic literature review approach has been used to understand the research gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept, in its various forms, is now acknowledged as a winning strategy for growth if not a fundamental one for survival in certain business environments (Ismail and Sharifi, 2006). Defined as a supply chain's capability to adapt or respond in a speedy manner to a changing market place environment (Swafford et al, 2005), and aimed to respond quickly to the unique needs of customers and markets, mastering change and uncertainty, leveraging the impact of the people, and enrich customers (Yusuf et al,2004), SCA helps firms to overcome all types of changes that exists in the business environment, such as, market volatility, intense competition, changes in customer's requirements, accelerating technological change, and changes in social factors (Lin et al, 2006;Du et al, 2021), resulting in more differentiation and increased profitability (Um, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The driver behind agility in manufacturing was the need to find a revolutionary way of manufacturing products while being able to manage uncertainties, and product introduction time to achieve responsiveness, innovation, superior quality, maximization of profit, and to satisfy the ever-increasing customer demand (Potdar et al, 2017). As the concept of agility evolved and was introduced to supply chains, researchers have classified the drivers behind agility in the supply chain in five broad areas including market volatility, intense competition, changes in customer requirements, accelerating technological change, and change in social factors (Lin et al, 2006;Du et al, 2021). It was also suggested that SCA is one of the most important strategies needed to face these changes with its objectives of establishing a Seamless Supply Chain (SSC) in which all players think and act as one, ensuring end customer satisfaction, having the ability to respond quickly and efficiently to a volatile marketplace (Mason and Towill, 1999;Power et al, 2001;Du et al, 2021), enriching customers and employees (Lin et al, 2006), anticipating uncertainties (Baramichai et al, 2006), reducing inventory, and integrating with suppliers more effectively (Faisal et al, 2007).…”
Section: Introductionmentioning
confidence: 99%